Silicon-containing oligomer and curable resin composition
A silicon-containing oligomer with a specific molecular structure addresses the brittleness and hydrolysis issues of crosslinked prepolymers, offering enhanced hydrolysis resistance, toughness, and improved curing characteristics.
Patent Information
- Application Number
- JP2023112081
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-20
AI Technical Summary
Crosslinked prepolymers such as epoxy resins suffer from brittleness, reduced adhesion, and compromised properties like heat resistance, moldability, and workability when efforts are made to improve mechanical strength, leading to issues like increased viscosity and hydrolysis of Si-O-Si bonds.
A silicon-containing oligomer with a specific molecular structure, obtained through a reaction of compounds represented by certain formulas, featuring a number average molecular weight of 700 or more, and having vinyl groups at the terminal, which enhances hydrolysis resistance and curability.
The silicon-containing oligomer exhibits improved hydrolysis resistance, lower curing shrinkage, and superior toughness, maintaining high heat resistance and mechanical strength while reducing water absorption and viscosity.
Smart Images

Figure 2025009224000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon-containing oligomer and a curable resin composition. [Background technology]
[0002] Crosslinked prepolymers such as epoxy resins and unsaturated polyester resins are excellent in, for example, heat resistance, insulating properties, adhesive properties, etc. Therefore, crosslinked prepolymers are widely used industrially as materials for composite structure applications and electrical and electronic applications.
[0003] However, crosslinked prepolymers have the problem of being brittle (hereinafter also simply referred to as "brittle") and the accompanying problem of reduced adhesiveness, which must be improved. When crosslinked prepolymers are improved to solve these problems, other properties such as heat resistance, moldability, and workability are sacrificed, which may limit their use.
[0004] For example, in Patent Document 1, the smaller the molecular weight of the epoxy resin as a crosslinked prepolymer, the more significant the brittleness of the cured product becomes, so that the molecular weight of the epoxy resin is increased to increase the mechanical strength of the cured product. However, simply increasing the molecular weight of the epoxy resin increases the viscosity of the prepolymer, decreasing workability and processability. In addition, there is a problem that the heat resistance (Tg) of the cured product is significantly decreased because the molecular weight between crosslinks of the cured product increases (i.e., the crosslink density decreases). Furthermore, since epoxy resin generates hydroxyl groups during the curing reaction, the water absorption and moisture absorption of the cured product increases, which results in a problem that electrical properties such as the dielectric constant and dielectric loss tangent are reduced.
[0005] In order to overcome such problems associated with epoxy resins, techniques have been reported that use a vinylsilyl group as a functional group instead of an epoxy group (for example, Patent Document 2, Patent Document 3, Non-Patent Document 1, and Non-Patent Document 2).
[0006] Among these techniques, Patent Document 2 describes that toughness is improved by introducing a flexible silicon-containing structure into a crosslinked prepolymer. However, Patent Document 2 has an industrial problem that hydrolysis or cleavage of the -Si-O-Si- bond occurs during the synthesis stage or the crosslinking (curing) stage because the basic skeleton and the terminal structure have a -Si-O-Si- structure with low bond stability. This crosslinked prepolymer also has a problem that the heat resistance and elastic modulus of the cured product are significantly reduced because the basic skeleton contains many flexible -Si-O-Si- structures.
[0007] Patent Document 3 describes a polyphenylene ether resin having dimethylvinylsilyl groups introduced at both ends. In this polyphenylene ether resin, the hydrolysis of the -Si-O-Si- bond as described above is suppressed, and the chemical stability is significantly improved. However, since the main skeleton is composed of a molecular chain of polyphenylene ether with low mobility, the viscosity of the prepolymer itself becomes high when melted, which is a problem that applicable compounding processes and curing processes are limited.
[0008] Non-Patent Documents 1 and 2 describe a monomer having vinylsilyl groups introduced at both ends, and a crosslinked polymer and a linear polymer containing silicon obtained by hydrosilylation of the monomer with a bifunctional SiH compound. However, the vinylsilyl groups contained in the monomer and the polymer are easily hydrolyzed, and therefore the monomer and the polymer have low moisture resistance and are easily hydrolyzed during the synthesis, blending, curing, and practical application stages. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] WO 2021 / 79812 [Patent Document 2] International Publication No. 2018 / 147010 [Patent Document 3] International Publication No. 2022 / 239631 [Non-patent literature]
[0010] [Non-Patent Document 1] Mollie B. Schear, et al., J. POLYM. SCI, A, 2014, 52, 523-526 [Non-Patent Document 2] Mollie B. Schear, et al., J. Appl. Polym. Sci. 2021, 138, e50053. Summary of the Invention [Problem to be solved by the invention]
[0011] Therefore, an object of the present invention is to provide a silicon-containing oligomer that is resistant to hydrolysis and has good curability, and a curable resin composition that contains the silicon-containing oligomer. [Means for solving the problem]
[0012] Means for Solving the Problems of the Prior Art The present inventors conducted intensive research to solve the above-mentioned problems of the prior art, and as a result of intensive investigation into a structure that can further suppress the hydrolysis of silyl groups and a silicon-containing oligomer structure that can suitably give a cured product that has less cure shrinkage and excellent toughness upon curing, they were able to complete the present invention.
[0013] That is, the present invention is as follows. [1] A silicon-containing oligomer having a number average molecular weight of 700 or more, obtained by reacting a compound represented by the following formula (1) with a compound represented by the following formula (4):
[0014] [ka]
[0015] (In formula (1), Q1's each independently represent an alkyl group having 1 to 3 carbon atoms, k's each independently represent an integer of 0 to 5, and A1 is a structure represented by the following formula (2) or (3).)
[0016] [ka]
[0017] (In formula (2), R1 is independently an alkyl group having 1 to 4 carbon atoms, m1 is independently an integer of 0 to 4, at least one of the two m1 is an integer of 1 or more, and A2 is a direct bond or a structure selected from the group consisting of the following formulae (i) to (vii).)
[0018] [ka]
[0019] [ka]
[0020] (In formula (3), each R2 independently represents an alkyl group having 1 to 4 carbon atoms, and each m2 independently represents an integer of 1 to 4.)
[0021] [ka]
[0022] (In formula (4), Q2 each independently represents an alkyl group having 1 to 3 carbon atoms, and B1 has a structure represented by the following formula (5) or (6).)
[0023] [ka]
[0024] (In formula (5), each R3 independently represents an alkyl group having 1 to 4 carbon atoms, each m3 independently represents an integer of 0 to 4, and B2 represents a direct bond or an -O- group.)
[0025] [ka]
[0026] (In formula (6), R4's each independently represent an alkyl group having 1 to 4 carbon atoms, and m4 represents an integer of 0 to 4).
[0027] [2] The silicon-containing oligomer according to [1], wherein A1 in the formula (1) is a structure represented by the following formula (7) or a structure represented by the following formula (8).
[0028] [ka]
[0029] (In formula (7), A2 has the same meaning as A2 in formula (2)).
[0030] [ka]
[0031] [3] The silicon-containing oligomer according to [1] or [2], wherein A1 in the formula (1) is a structure represented by the following formula (9):
[0032] [ka]
[0033] [4] The silicon-containing oligomer according to any one of [1] to [3], wherein the compound represented by formula (4) is a compound represented by the following formula (13) or a compound represented by the following formula (14):
[0034] [ka]
[0035] [ka]
[0036] [5] The silicon-containing oligomer according to any one of [1] to [4], wherein at least one terminal of the molecular chain is a vinyl group.
[0037] [6] The silicon-containing oligomer according to any one of [1] to [5], which has a number average molecular weight of 2,000 or more.
[0038] [7] A curable resin composition comprising the following component (A) and the following component (B): (A): A silicon-containing oligomer according to any one of [1] to [6] (B): Polymerization initiator
[0039] [8] The curable resin composition according to [7], wherein the polymerization initiator is an organic peroxide.
[0040] [9] The curable resin composition according to [7], further comprising the following component (C): (C): Organic solvent Effect of the Invention
[0041] According to the present invention, it is possible to obtain a silicon-containing oligomer having hydrolysis resistance and good curability, and a curable resin composition containing the silicon-containing oligomer. [Brief description of the drawings]
[0042] [Figure 1] 1 shows the results of NMR measurement of the diallylated tetramethylbiphenyl (VS-TMBP) purified in Example 1. [Diagram 2] 1 shows the molecular weight distribution of silicon-containing oligomer A of Example 1 as measured by GPC. [Diagram 3] 1 shows the results of NMR measurement of silicon-containing oligomer A of Example 1. [Figure 4]1 shows the results of NMR measurement of 4,4'-[(dimethylvinylsilyl)oxy]biphenyl of Comparative Example 1. [Diagram 5] In Comparative Example 1, the NMR measurement results of 4,4'-[(dimethylvinylsilyl)oxy]biphenyl after the hydrolysis resistance test are shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0043] Hereinafter, an embodiment of the present invention (hereinafter also simply referred to as "the present embodiment") will be described in detail. The following embodiment is an example for explaining the present invention, and the present invention is not limited to this embodiment, and the present invention can be practiced by appropriately modifying it within the scope of its gist.
[0044] [Silicon-containing oligomer] The silicon-containing oligomer of the present embodiment is obtained by reacting a compound represented by the following formula (1) with a compound represented by the following formula (4), and has a number average molecular weight of 700 or more.
[0045] [ka]
[0046] [ka]
[0047] The silicon-containing oligomer of this embodiment is preferably obtained by a reaction in the presence or absence of a metal catalyst. More preferably, the silicon-containing oligomer of this embodiment has at least one terminal of the molecular chain being a vinyl group.
[0048] <Q1 in formula (1)> In formula (1), each Q1 is independently an alkyl group having 1 to 3 carbon atoms. The larger the carbon number, the lower the water absorption rate of the cured product of the silicon-containing oligomer. Also, the smaller the carbon number, the lower the viscosity of the silicon-containing oligomer. From this viewpoint, the carbon number is preferably 1 or 2, and more preferably 1.
[0049] <k in formula (1)> In formula (1), each k is independently an integer of 0 to 5. The larger k is, the lower the viscosity of the silicon-containing oligomer tends to be. Also, the smaller k is, the higher the heat resistance of the cured product of the silicon-containing oligomer tends to be. From this viewpoint, the value of k is preferably an integer of 0 to 3, more preferably 0 or 1, and even more preferably 0.
[0050] <A1 in formula (1)> A1 in formula (1) is a structure represented by the following formula (2) or (3).
[0051] [ka]
[0052] [ka]
[0053] <A2 in formula (2)> A2 in formula (2) represents a direct bond and a structure selected from the group consisting of the following formulae (i) to (vii).
[0054] [ka]
[0055] The structure of A1 in formula (1) tends to have higher heat resistance of the cured product as the structure has higher rigidity and planarity. From such a viewpoint, the structure of A2 in formula (2) is preferably a structure in which the π electrons of the directly bonded phenylene group tend to be delocalized, more preferably a structure selected from the group consisting of a direct bond, and formulae (i), (ii), (iv), and (vii), and further preferably a direct bond.
[0056] <R1 in formula (2)> In formula (2), R1's are each independently an alkyl group having 1 to 4 carbon atoms. The smaller the carbon number, the higher the heat resistance of the cured product of the silicon-containing oligomer tends to be. The larger the carbon number, the lower the water absorption of the cured product of the silicon-containing oligomer tends to be. From this viewpoint, R1 in formula (2) is preferably an alkyl group having 1 to 2 carbon atoms, more preferably an alkyl group having 1 carbon atom. The groups other than R1 bonded to the phenyl group are hydrogen atoms.
[0057] <m1 in formula (2)> In formula (2), each m1 is independently an integer of 0 to 4, and at least one of the two m1's is an integer of 1 or greater. In general, the -Si-O- bond directly connected to a phenyl group tends to be easily hydrolyzed at the bond between Si and O. However, when at least one position of the phenyl group is substituted with an alkyl group, the hydrolysis of the -Si-O- bond tends to be more suppressed. When the ortho position of the phenyl group with respect to the -Si-O- bond is substituted with an alkyl group, the hydrolysis resistance tends to be significantly improved. The smaller m1 is, the lower the viscosity of the silicon-containing oligomer tends to be. The larger m1 is, the lower the water absorption rate of the cured product of the silicon-containing oligomer tends to be. From such a viewpoint, m1 is preferably an integer of 1 to 3, more preferably 2.
[0058] <R2 in formula (3)> In formula (3), R2's are each independently an alkyl group having 1 to 4 carbon atoms. The smaller the carbon number, the higher the heat resistance of the cured product of the silicon-containing oligomer tends to be. The larger the carbon number, the lower the water absorption of the cured product of the silicon-containing oligomer tends to be. From this viewpoint, R1 is preferably an alkyl group having 1 to 2 carbon atoms, more preferably an alkyl group having 1 carbon atom. The group other than R2 bonded to the phenyl group is a hydrogen atom.
[0059] <m2 in formula (3)> In the formula (3), each m2 is independently an integer of 1 to 4. In general, the -Si-O- bond directly connected to a phenyl group tends to be easily hydrolyzed at the bond between Si and O. However, when at least one position of the phenyl group is substituted with an alkyl group, the hydrolysis of the -Si-O- bond tends to be significantly suppressed. The smaller m2 is, the higher the heat resistance of the cured product of the silicon-containing oligomer tends to be. The larger m2 is, the lower the water absorption rate of the cured product of the silicon-containing oligomer tends to be. From this viewpoint, m1 is preferably an integer of 2 to 4, more preferably 3.
[0060] In the structure of A1 in formula (1), it is preferable that more alkyl groups are substituted at the ortho positions of the -Si-O- bond directly connected to A1. With such a structure, the silicon-containing oligomer cured product tends to have a better balance between high heat resistance and low water absorption.
[0061] From this viewpoint, A1 in formula (1) is preferably a structure of the following formula (7) or a structure of the following formula (8).
[0062] [ka]
[0063] In formula (7), A2 has the same meaning as A2 in formula (2).
[0064] [ka]
[0065] Further, the structure of A1 in formula (1) is more preferably a structure in which all of the ortho positions of the -Si-O- bond directly bonded to A1 are substituted with alkyl groups. From this viewpoint, A1 in formula (1) preferably represents one structure selected from the group consisting of the following formulae (9) to (12), and more preferably the structure of formula (9).
[0066] [ka]
[0067] [ka]
[0068] [ka]
[0069] [ka]
[0070] <Q2 in formula (4)> In the formula (4), each Q2 independently represents an alkyl group having 1 to 3 carbon atoms. The larger the carbon number, the lower the water absorption rate of the cured product of the silicon-containing oligomer. The smaller the carbon number, the lower the viscosity of the silicon-containing oligomer. From this viewpoint, the carbon number is preferably 1 or 2, and more preferably 1. It is further preferable that all Q2 in formula (4) are methyl groups.
[0071] <B1 in formula (4)> B1 in the formula (4) is a structure represented by the following formula (5) or (6).
[0072] [ka]
[0073] [ka]
[0074] <B2 in formula (5)> B2 in formula (5) represents a direct bond or an -O- group. When B2 is a direct bond, the melting point (Tg) of the cured product of the silicon-containing oligomer tends to be high. When B2 is an -O- group, the viscosity of the silicon-containing oligomer tends to be low, and the workability and moldability at the curing stage tend to be excellent. In this specification, the melting point (°C) of the cured product of the silicon-containing oligomer can be measured, for example, by DSC (differential scanning calorimeter).
[0075] <R3 in formula (5)> In the formula (5), each R3 independently represents a hydrocarbon group having 1 to 4 carbon atoms. The smaller the carbon number, the higher the melting point (Tg) of the cured product of the silicon-containing oligomer tends to be. The larger the carbon number, the lower the moisture absorption of the cured product of the silicon-containing oligomer tends to be. From this viewpoint, R3 preferably has 1 to 2 carbon atoms, and more preferably has 1 carbon atom. The group other than R3 bonded to the phenyl group is a hydrogen atom.
[0076] <m3 in formula (5)> In the formula (5), m3 each independently represents an integer of 0 to 4. The smaller m3, the higher the melting point (Tg) of the cured product of the silicon-containing oligomer tends to be. The larger m3, the lower the moisture absorption of the cured product of the silicon-containing oligomer tends to be. From this viewpoint, m3 is preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0077] <R4 in formula (6)> In the formula (6), R4's each independently represent an alkyl group having 1 to 4 carbon atoms. The smaller the carbon number, the higher the melting point (Tg) of the cured product of the silicon-containing oligomer tends to be. The larger the carbon number, the lower the moisture absorption of the cured product of the silicon-containing oligomer tends to be. From this viewpoint, R4 preferably has 1 to 2 carbon atoms, and more preferably has 1 carbon atom.
[0078] <m4 in formula (6)> In the formula (6), each m4 independently represents an integer of 0 to 4. The smaller m4 is, the higher the melting point (Tg) of the cured product of the silicon-containing oligomer tends to be. The larger m4 is, the lower the moisture absorption of the cured product of the silicon-containing oligomer tends to be. From such a viewpoint, m4 is preferably an integer of 0 to 2, more preferably 0 or 1, and even more preferably 0.
[0079] From the above viewpoints, B1 in formula (4) is preferably a structure of the following formula (15) or (16).
[0080] [ka]
[0081] [ka]
[0082] The compound represented by formula (4) is preferably a compound represented by the following formula (13) or a compound represented by the following formula (14). When the compound represented by formula (4) is such a compound, the viscosity of the silicon-containing oligomer becomes better, and the water absorption, melting point (Tg), and hygroscopicity of the cured product of the silicon-containing oligomer tend to be superior.
[0083] [ka]
[0084] [ka]
[0085] <Number average molecular weight> The number average molecular weight (Mn) of the silicon-containing oligomer is 700 or more. If the number average molecular weight is less than 700, the toughness of the cured product of the silicon-containing oligomer is reduced. The larger the number average molecular weight, the smaller the cure shrinkage of the cured product of the silicon-containing oligomer tends to be. The smaller the number average molecular weight, the lower the viscosity of the silicon-containing oligomer and the more excellent the moldability tends to be. From such a viewpoint, the number average molecular weight is preferably 700 to 100,000, more preferably 1,000 to 100,000, even more preferably 2,000 to 60,000, even more preferably 3,000 to 30,000, and even more preferably 5,000 to 10,000. In this specification, Mw indicates the weight average molecular weight, Mn indicates the number average molecular weight, and Mw / Mn indicates the molecular weight distribution. Mw, Mn, and molecular weight distribution (Mw / Mn) can be determined by gel permeation chromatography (GPC) using polystyrene standard. For specific measurement methods, refer to the Examples.
[0086] <Silicon-containing oligomer> The silicon-containing oligomer of the present embodiment is preferably at least one selected from the group consisting of a compound represented by the following formula (17), a compound represented by the following formula (18), and a compound represented by the following formula (19). It is more preferable that the silicon-containing oligomer contains a compound represented by the following formula (17).
[0087] [ka]
[0088] In formula (17), Q1, k, and A1 are respectively defined as Q1, k, and A1 in formula (1). In formula (17), Q2 and B1 are respectively defined as Q2 and B1 in formula (4). In formula (17), l represents a real number greater than 0. The range of l is determined by the number average molecular weight and varies depending on the specific chemical structure of the molecular skeleton, but is generally 0.1 to 500, preferably 1 to 100, and more preferably 10 to 50.
[0089] [ka]
[0090] In formula (18), Q1, k, and A1 are respectively defined as Q1, k, and A1 in formula (1). In formula (18), Q2 and B1 are respectively defined as Q2 and B1 in formula (4). In formula (18), m is a real number greater than 0. The range of m is determined by the number average molecular weight and varies depending on the specific chemical structure of the molecular skeleton, but is generally 0.1 to 500, preferably 1 to 100, and more preferably 10 to 50.
[0091] [ka]
[0092] In formula (19), Q1, k, and A1 are respectively defined as Q1, k, and A1 in formula (1). In formula (19), Q2 and B1 are respectively defined as Q2 and B1 in formula (4). In formula (19), n is a real number greater than 0. The range of n is determined by the number average molecular weight and varies depending on the specific chemical structure of the molecular skeleton, but is generally 0.1 to 500, preferably 1 to 100, and more preferably 10 to 50.
[0093] l in formula (17), m in formula (18), and n in formula (19) each represent the number of repetitions, and in the molecular structure of each molecule, represent a real number greater than 0. These values have the character of number average values, since the resulting silicon-containing oligomer is composed of a mixture of various molecules, and are limited by the number average molecular weight.
[0094] [Method for producing silicon-containing oligomer] (Step-growth polymerization reaction) <Ratio of vinyl groups to SiH during reaction> The silicon-containing oligomer of this embodiment can be obtained by sequential polymerization of a compound having a terminal carbon-carbon double bond represented by the above formula (1) and a compound having a terminal SiH group represented by the above formula (4) in the presence or absence of a metal catalyst. By appropriately adjusting the molar ratio r (r=SiH / double bond (mol / mol)) of the carbon-carbon double bond and the SiH group at this time, the structure and number average molecular weight of the obtained silicon-containing oligomer can be controlled.
[0095] By carrying out the reaction at a molar ratio r of less than 1, it is possible to more reliably synthesize a silicon-containing oligomer having a terminal carbon-carbon double bond. By carrying out the reaction at a molar ratio r of more than 1, it is possible to more reliably synthesize a silicon-containing oligomer having a terminal SiH group.
[0096] There is a tendency that a silicon-containing oligomer having a larger number average molecular weight can be obtained as the molar ratio r approaches 1. From this viewpoint, the molar ratio r is preferably 0.5 to 2.0, more preferably 0.7 to 1.4, even more preferably 0.8 to 1.3, and even more preferably 0.9 to 1.1.
[0097] <Metal catalyst> When a metal catalyst is used in the reaction of the compound represented by formula (1) with the compound represented by formula (4), side reactions can be suppressed, and a silicon-containing oligomer with high purity tends to be obtained. Therefore, it is preferable to use a metal catalyst in the sequential polymerization reaction. Examples of the metal catalyst include platinum (Pt), palladium (Pd), and tin (Sn). As the metal catalyst, a Pt-containing catalyst is preferable because it tends to make the reaction proceed more quickly.
[0098] Such Pt-containing catalysts include, for example, platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex, [1,3-Bis(cyclohexyl)imidazol-2-ylidene][1,3-divinyl-1,1,3,3-tetramethyldisiloxane]platinum(0), trimethyl(methylcyclopentadienyl)platinum(IV), [1,3-Bis(2,6-diisopropylphenyl)-imidazolidinylidene][1,3-divinyl-1,1,3,3-tetramethyldisiloxane]platinum(0), and [1,3-Bis(2,6-diisopropylphenyl)imidazol-2-ylidene][1,3-divinyl-1,1,3,3-tetramethyldisiloxane]platinum(0).
[0099] As the Pt-containing catalyst, a platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex and a compound of a platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex and [1,3-Bis(2,6-diisopropylphenyl)imidazol-2-ylidene][1,3-divinyl-1,1,3,3-tetramethyldisiloxane]platinum(0) represented by the following formula (20) are preferred because they suppress side reactions and allow the polymerizing reaction to proceed more quickly. The compound represented by the following formula (20) may be a commercially available product, or a compound produced by a known method. An example of such a commercially available product is HS425 (trade name) manufactured by Umicore Japan Co., Ltd.
[0100] [ka]
[0101] <Amount of metal catalyst added> The amount of the metal catalyst added is preferably 10 ppm to 1000 ppm, and more preferably 100 ppm to 300 ppm, calculated as the weight of the metal, relative to the compound represented by formula (4).
[0102] <Sequential polymerization reaction temperature> The reaction temperature of the sequential polymerization reaction is usually in the range of room temperature to 250° C. The reaction temperature is preferably in the range of 40° C. to 120° C., and more preferably in the range of 50° C. to 100° C.
[0103] <Reaction solvent> When synthesizing silicon-containing oligomers by sequential polymerization reaction, an organic solvent can be used as a reaction solvent as necessary. Examples of such organic solvents include aromatic hydrocarbons such as toluene and xylene; aliphatic hydrocarbons such as hexane, cyclohexane, and heptane; esters such as ethyl acetate and n-butyl acetate; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; ethers such as tetrahydrofuran and dioxane; amides such as dimethylacetamide and dimethylformamide; halogen compounds such as chloroform, methylene chloride, and carbon tetrachloride; dimethylsulfoxide, and nitrobenzene. These organic solvents can be used alone or in combination of two or more. Among these, from the viewpoints of allowing the reaction to proceed more smoothly and the solvent to be distilled off more easily, it is preferable to use at least one selected from the group consisting of dioxane and tetrahydrofuran, and dioxane is more preferable.
[0104] [Curable resin composition] The curable resin composition of the present embodiment contains the following component (A) and the following component (B). (A): Silicon-containing oligomer of this embodiment (B): Polymerization initiator
[0105] (Curing reaction) <Polymerization initiator> The curable resin composition of the present embodiment may contain a polymerization initiator. The polymerization initiator is not particularly limited, but examples thereof include organic peroxides and metal catalysts such as Pt, Pd, and Sn. The polymerization initiator is preferably an organic peroxide.
[0106] When an organic peroxide is used as a polymerization initiator, the polymerization initiation temperature tends to be easier to control when polymerizing a silicon-containing oligomer having a high ratio of components terminated with double bonds. When a metal catalyst is used as a polymerization initiator, the polymerization reaction tends to proceed more quickly when polymerizing a silicon-containing oligomer having a high ratio of components terminated with SiH groups.
[0107] From the viewpoint of allowing the curable resin composition to be stored more stably and having more suitable reactivity, the organic peroxide is preferably an organic peroxide having a 1-minute half-life temperature in the range of 155 to 180° C. Examples of such organic peroxides include t-hexylperoxyisopropyl monocarbonate (155.0° C.), t-butylperoxy-3,5,5-trimethylhexanoate (166.0° C.), t-butylperoxylaurate (159.4° C.), t-butylperoxyisopropyl monocarbonate (158.8° C.), t-butylperoxy2-ethylhexyl monocarbonate (161.4° C.), t-hexylperoxybenzoate (160.3° C.), 2,5-dimethyl-2,5-di(benzoylperoxy)hexane (158.2 ...laurate (159.4° C.), t-butylperoxylaurate (159.4° C.), t-butylperoxylaurate (159.4° C.), t-butylperoxylaurate (159.4° C.), t-butylperoxylaurate (159.4° C.), t-butylperoxylaurate (159.4° C.), t-butylperoxylaurate (159.4° C.), t-butylperoxylaurate (159.4° C.), t-butylperoxylaurate ( Examples of organic peroxides include oxyacetate (159.9°C), 2,2-di-(t-butylperoxy)butane (159.9°C), t-butylperoxybenzoate (166.8°C), n-butyl 4,4-di-(t-butylperoxy)valerate (172.5°C), di(2-t-butylperoxyisopropyl)benzene (175.4°C), dicumyl peroxide (175.2°C), di-t-hexyl peroxide (176.7°C), 2,5-dimethyl-2,5-di(t-butylperoxy)hexane (179.8°C), and t-butylcumyl peroxide (173.3°C). The temperature in parentheses for organic peroxides indicates the 1-minute half-life temperature.
[0108] Among these, the organic peroxide is more preferably at least one selected from the group consisting of t-butyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, di(2-t-butylperoxyisopropyl)benzene, dicumyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and t-butylcumyl peroxide.
[0109] Examples of the metal catalyst include those exemplified as the metal catalyst used when reacting the compound represented by the above formula (1) with the compound represented by the above formula (4).
[0110] <Amount of polymerization initiator> In the curable resin composition, the amount of the polymerization initiator is preferably 0.001 to 10.0 phr based on the silicon-containing oligomer. When the amount of the polymerization initiator is 0.001 phr or more, the effect as a polymerization initiator is more fully exhibited, the progress of the curing reaction can be further promoted, and the melting point (Tg) of the cured product tends to be higher. When the amount of the polymerization initiator is 10.0 phr or less, the amount of the polymerization initiator and its decomposition product remaining in the cured product tends to be reduced. From such a viewpoint, the amount of the polymerization initiator is more preferably 0.1 to 5.0 phr, and further preferably 0.5 to 2.0 phr.
[0111] <Curing temperature> The silicon-containing oligomer can be cured by heating in the presence or absence of a polymerization initiator. The curing temperature is not particularly limited, but it can usually be cured within the range of room temperature to 350° C. The curing temperature is preferably 100° C. to 250° C., more preferably 120° C. to 230° C., and even more preferably 150° C. to 200° C.
[0112] <Curing time> The curing time is not particularly limited, but is usually 30 minutes to 10 hours, preferably 1 hour to 8 hours, and more preferably 2 hours to 5 hours.
[0113] <Solvent> The silicon-containing oligomer and the curable resin composition may contain an organic solvent or an inorganic solvent within the scope of the present invention.
[0114] The curable resin composition of the present embodiment preferably further contains the following component (C). (C): Organic solvent
[0115] Examples of the organic solvent include chloroform, carbon tetrachloride, methylene chloride, toluene, xylene, methyl ethyl ketone, methyl isobutyl ketone, dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), and ethyl acetate. Toluene and methyl ethyl ketone are preferred as the organic solvent because they have a lower boiling point and can be more easily removed by evaporation from the resin composition, and from the viewpoint of safety and hygiene.
[0116] <Additional materials> Additives such as inorganic fillers can be added to the silicon-containing oligomer and the curable resin composition as necessary, provided that the object of the present invention is not impaired.
[0117] Examples of inorganic fillers include silica powders such as spherical or crushed fused silica and crystalline silica, mica, talc, calcium carbonate, alumina, hydrated alumina, asbestos, magnesium oxide, diatomaceous earth, and graphite.
[0118] Examples of other additives include thixotropy imparting agents such as fine silica powder, antifoaming agents, flame retardants such as phosphorus compounds and halogen compounds, flame retardant assistants such as antimony trioxide, colorants such as carbon black and iron oxide, elastomers such as modified nitrile rubber and modified polybutadiene, release agents, leveling agents, anti-cissing agents, and antifoaming agents. Glass fibers, glass cloth, carbon fibers, etc. may also be contained as necessary.
[0119] According to the curing method of the present embodiment, when a crosslinked prepolymer is put to practical use, the problems of brittleness and adhesion caused by brittleness can be solved. When put to practical use, the cured product of the silicon-containing oligomer exhibits a sufficiently high melting point (Tg), higher toughness, moisture resistance, low water absorption, low cure shrinkage, dimensional stability, and electrical properties. EXAMPLES
[0120] Hereinafter, the present embodiment will be described in detail with reference to specific examples and comparative examples, but the present invention is not limited in any way to the following examples and comparative examples.
[0121] First, the methods for measuring and evaluating each physical property will be described below.
[0122] (1) Number average molecular weight (Mn) An LC-10AD (product name) manufactured by Shimadzu Corporation was used as a device for measuring the number average molecular weight of the silicon-containing oligomer, and a calibration curve was prepared using standard polystyrene. Using this calibration curve, the number average molecular weight (Mn) of the silicon-containing oligomers in the examples and comparative examples described below was measured. The standard polystyrenes used were those with molecular weights of 580, 1050, 1200, 1310, 1990, 2970, 4490, 5030, 6180, 6930, 10700, 16500, 19800, 55100, 133000, 288000, 666000, 1280000, and 2780000. The column used was two Shodex (registered trademark) LF-804 (product name) columns manufactured by Resonac Corporation connected in series. The solvent used was tetrahydrofuran (THF), the flow rate of the solvent was 1.0 mL / min, and the column temperature was 40°C. The detector used was a differential refractive index detector (RID-10A (product name), manufactured by Shimadzu Corporation). The number average molecular weight (Mn) was calculated from the ratio of peak areas based on a curve showing the molecular weight distribution (Mw / Mn) obtained by GPC (gel permeation chromatography) based on the above measurement data.
[0123] (2) Identification of chemical structure by NMR measurement Regarding silicon-containing oligomers, 1 The chemical structure was identified by H-NMR measurement. Measurement equipment: Superconducting Fourier transform nuclear magnetic resonance measurement equipment (JNM-EX400 (product name), manufactured by JEOL Ltd.) Sample amount: approx. 1.0 mg Measurement solvent: deuterated chloroform (CDCl3), deuterated dimethyl sulfoxide (DMSO) approx. 5 mL Internal standard: Tetramethylsilane (TMS) Magnetic strength: 400MHz Number of times: 16
[0124] (3) Evaluation of hydrolysis resistance The silicon-containing oligomers of the examples and comparative examples described below were used as evaluation samples, and the hydrolysis resistance was evaluated using the evaluation samples. Specifically, the evaluation samples were stored for 3 days under conditions of 15°C to 35°C and humidity of 30% to 80%, and the remaining proportion of vinyl groups before and after the storage was measured. 1 The measurement results were then used to evaluate the hydrolysis resistance according to the following criteria. [Evaluation Criteria] A: The remaining vinyl group ratio is 80% or more. B: The remaining proportion of vinyl groups is 50% or more and less than 80%. C: The remaining proportion of vinyl groups is less than 50%.
[0125] (4) Resilience assessment The silicon-containing oligomer or its cured product of the examples and comparative examples described below was used as an evaluation sample, and the toughness was evaluated using the evaluation sample. Specifically, a tensile property test was carried out under the following conditions, and the fracture energy was calculated from the area under the downward pressure of the obtained stress-strain curve to evaluate the toughness. Note that the larger the fracture energy, the more excellent the toughness of the silicon-containing oligomer or its cured product. [Conditions for tensile property test] Test equipment: Instron type tensile testing machine (AGS-J (product name), manufactured by Shimadzu Corporation) Crosshead speed: 2mm / min, Maximum load: 100kgf Evaluation sample: 1BB type test piece (1 / 5) Size: Total length: 30 mm, width: 4 mm, thickness: 2 mm Length of parallel part: 12mm, Width of parallel part: 2mm, Radius of roundness: 12mm Grip distance: 24 mm, gauge distance: 10 mm
[0126] (5) Evaluation of adhesive strength The silicon-containing oligomers of the examples and comparative examples described below were used as evaluation samples, and the adhesive strength was evaluated using the evaluation samples. Specifically, a tensile shear adhesive strength test was carried out under the following conditions in accordance with JIS K6850:1999 (ISO 4587:1995) to evaluate the adhesive strength. Note that the higher the breaking strength, the more excellent the adhesiveness of the cured product. The evaluation samples were prepared by the following method. First, a 3.2 mm thick mild steel plate was washed with acetone, and then the surface of the mild steel plate was polished with No. 240 abrasive paper. Dirt such as polishing powder adhering to the surface of the mild steel plate was wiped off with absorbent cotton. Then, the silicon-containing oligomer of the below-mentioned Examples and Comparative Examples was applied to a predetermined area of the mild steel plate, fixed with clips, and cured under predetermined conditions. The cured product was used as the evaluation sample. The results were then used to evaluate the adhesive strength according to the following criteria. [Tensile shear adhesive strength test] Mild steel plate size: Length 100±0.25mm x Width 25.0±0.25mm x Thickness 1.6±0.1mm Overlap length: 12.5±0.25mm Recommended adhesive layer thickness: 0.2mm [Evaluation Criteria]
[0127] (6) Evaluation of fracture toughness The silicon-containing oligomer or its cured product of the examples and comparative examples described below is used as an evaluation sample, and the fracture toughness is evaluated using the evaluation sample. Specifically, the evaluation sample is measured by a three-point bending test in accordance with ASTM D5045 to obtain a fracture toughness value, and the fracture toughness is evaluated. Note that the larger the fracture toughness value, the more excellent the fracture toughness of the silicon-containing oligomer or its cured product.
[0128] (7) Measurement of Tg of cured product (DMA method) The glass transition temperature (Tg) of the cured product of the silicon-containing oligomer was measured by dynamic viscoelasticity measurement under the following conditions. The measurements were performed in a tensile mode using a non-resonant forced vibration type viscoelasticity measurement analyzer (Rheogel-E4000 (product name), manufactured by UBM Co., Ltd.). In this measurement, the peak temperature of tan δ was taken as the glass transition temperature (Tg, ° C.) of the cured product. <Measurement conditions> Sample size: 30mm x 4.0mm x 0.8mm Waveform: Sine wave Frequency: 10Hz Displacement amplitude: 5μm Measurement temperature: -150~250℃ Heating rate: 2℃ / min
[0129] [Silicon-containing oligomer A] Example 1 <Synthesis of diallylated tetramethylbiphenyl (compound represented by formula (1))> In a 300 mL eggplant flask, add 12.1 g (5.0 × 10 -2 mol) was added, 120 g of 1,4-dioxane was further added and completely dissolved, and then 24.2 g (2.4 × 10 -1 mol) and 0.246 g (2.0 × 10 -3 mol) was added to obtain mixed solution A.
[0130] Then, 14.5 g (1.2 × 10 -1 A mixed solution of 14.6 g of 1,4-dioxane and 13.5 mol was added dropwise to mixed solution A over 15 minutes under a nitrogen atmosphere (nitrogen flow rate: 500 mL / min), and the mixture was stirred at 60° C. for 2 hours under a nitrogen atmosphere (nitrogen flow rate: 500 mL / min). After stirring, 3.85 g of methanol was added to quench unreacted chlorodimethylvinylsilane.
[0131] Thereafter, suction filtration was carried out, and the solvent was removed from the resulting solution using an evaporator at 110° C. to obtain 18.1 g of a diallylated product of tetramethylbiphenyl (VS-TMBP) with a yield of 88%. Next, 5 g of the obtained VS-TMBP was dissolved in 50 g of hexane, and then 20 g of acetonitrile was added to perform extraction. After extraction, the lower layer, the acetonitrile solution, was removed. This extraction procedure was repeated three times.
[0132] The solvent of the resulting hexane solution was then removed using an evaporator to obtain purified VS-TMBP represented by the following formula (21). The NMR measurement results of the purified VS-TMBP are shown in Figure 1.
[0133] [ka]
[0134] <Synthesis of silicon-containing oligomer A> Next, 2.06 g (5.0 × 10) of purified VS-TMBP was added to a 100 mL eggplant flask. -3 mol), 20 g of 1,4-dioxane, and 0.87 g (4.5 × 10 mol) of 1,4-bis(dimethylsilyl)benzene, which is 0.9 times the molar amount of the purified VS-TMBP. -3 mol) and 1.46 × 10 2% xylene solution of platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex as a catalyst. -2g (140 ppm by weight of platinum relative to VS-TMBP) was added. The mixture was then stirred at 90°C for 3 hours under a nitrogen atmosphere (nitrogen flow rate 500 mL / min) to react. After stirring, the reaction solution was evaporated at 150°C for 1 hour to remove 1,4-dioxane, and 2.80 g of silicon-containing oligomer A was obtained in a yield of 96%.
[0135] GPC measurement revealed that the number average molecular weight of silicon-containing oligomer A was 4850. The molecular weight distribution of silicon-containing oligomer A measured by GPC is shown in FIG. FIG. 3 shows the NMR measurement results of silicon-containing oligomer A. When the hydrolysis resistance test of Oligomer A was carried out, the residual rate of vinyl groups was found to be 95% or more. As a result, the hydrolysis resistance was evaluated as A, and it was found that Silicon-containing Oligomer A has excellent hydrolysis resistance.
[0136] (Application Example 1) 2 g of silicon-containing oligomer A and 0.02 g of Perbutyl (registered trademark) P (trade name, manufactured by NOF Corp., α,α-di(t-butylperoxy)diisopropylbenzene) were dissolved in acetone, and then the acetone was removed using a rotary evaporator to obtain a solid resin composition A. The solid resin composition A was pulverized in an agate mortar and then placed in an aluminum cup (5 mm x 30 mm). The aluminum cup was placed on a hot plate with a vacuum chamber and heated at 120°C for 40 minutes under reduced pressure to perform a degassing treatment to obtain a composition A. Thereafter, the composition A was heated at 180°C for 1 hour, further heated at 220°C for 1 hour, and further heated at 300°C for 1 hour to cure the composition A and obtain a cured product A. The Tg of the cured product A was measured by the above-mentioned DMA method and was found to be 80°C.
[0137] [4,4'-[(dimethylvinylsilyl)oxy]biphenyl] Comparative Example 1 <Synthesis of 4,4'-[(dimethylvinylsilyl)oxy]biphenyl> In a 100 mL eggplant flask, add 3.72 g (2.0 × 10 -2 mol) was added, 37.2 g of 1,4-dioxane was further added and completely dissolved, and then 9.70 g (9.6 × 10 -2 mol) and 4-dimethylaminopyridine 8.0 × 10 -4 mol was added to obtain mixed solution a.
[0138] Then, 5.80 g (4.8 × 10 -2 A mixed solution of 5.93 g of 1,4-dioxane and 5.89 mol was added dropwise to the mixed solution a over 15 minutes, and the mixture was stirred at room temperature for 2 hours. The liquid temperature was then raised to 60° C., and the mixture was further stirred at that temperature for 2 hours.
[0139] After stirring, 1.58 g of methanol was added to quench unreacted chlorodimethylvinylsilane.
[0140] Thereafter, suction filtration was carried out, and the solvent was removed from the resulting solution using an evaporator at 110° C. for 0.5 hours to obtain 6.07 g of a brown liquid, the yield being 89%.
[0141] The brown liquid was analyzed by NMR and the product was confirmed to be 4,4'-[(dimethylvinylsilyl)oxy]biphenyl. The NMR measurement result of 4,4'-[(dimethylvinylsilyl)oxy]biphenyl is shown in Figure 4. The hydrolysis resistance test of the obtained 4,4'-[(dimethylvinylsilyl)oxy]biphenyl showed that the residual rate of vinyl groups was 48%. As a result, the evaluation result of hydrolysis resistance was C, and it was found that 4,4'-[(dimethylvinylsilyl)oxy]biphenyl has poor hydrolysis resistance. FIG. 5 shows the NMR measurement results of 4,4'-[(dimethylvinylsilyl)oxy]biphenyl after the hydrolysis resistance test.
Claims
1. A silicon-containing oligomer having a number average molecular weight of 700 or more, obtained by reacting a compound represented by the following formula (1) with a compound represented by the following formula (4): 【Chemistry 1】 (In formula (1), Q 1 each independently represents an alkyl group having 1 to 3 carbon atoms; each k independently represents an integer of 0 to 5; 1 is a structure of the following formula (2) or the following formula (3). 【Chemistry 2】 (In formula (2), R 1 are each independently an alkyl group having 1 to 4 carbon atoms; 1 are each independently an integer of 0 to 4, and two m 1 At least one of A is an integer of 1 or more; 2 represents a direct bond and one structure selected from the group consisting of the following formulas (i) to (vii): 【Chemistry 3】 【Chemistry 4】 (In formula (3), R 2 each independently represents an alkyl group having 1 to 4 carbon atoms; 2 each independently represents an integer of 1 to 4.) 【Chemistry 5】 (In formula (4), Q 2 each independently represents an alkyl group having 1 to 3 carbon atoms; B 1 is a structure of the following formula (5) or the following formula (6). 【Chemistry 6】 (In formula (5), R 3 each independently represents an alkyl group having 1 to 4 carbon atoms; 3 each independently represents an integer of 0 to 4; B 2 represents a direct bond or an --O-- group. 【Chemistry 7】 (In formula (6), R 4 each independently represents an alkyl group having 1 to 4 carbon atoms; 4 represents an integer from 0 to 4.
2. A in the formula (1) 1 The silicon-containing oligomer according to claim 1 , wherein: 【Chemistry 8】 (In formula (7), A 2 is A in formula (2). 2 is synonymous with.). 【Chemistry 9】
3. A in the formula (1) 1 The silicon-containing oligomer according to claim 1 , wherein the silicon-containing oligomer has a structure represented by the following formula (9): 【Chemistry 10】
4. The silicon-containing oligomer according to claim 1, wherein the compound represented by formula (4) is a compound represented by the following formula (13) or a compound represented by the following formula (14): 【Chemistry 11】 【Chemistry 12】
5. 2. The silicon-containing oligomer according to claim 1, wherein at least one terminal of the molecular chain is a vinyl group.
6. The silicon-containing oligomer according to claim 1 , having a number average molecular weight of 2,000 or more.
7. A curable resin composition comprising the following component (A) and the following component (B): (A): The silicon-containing oligomer according to any one of claims 1 to 6 (B): Polymerization initiator
8. The curable resin composition according to claim 7 , wherein the polymerization initiator is an organic peroxide.
9. The curable resin composition according to claim 7, further comprising the following component (C): (C): Organic solvent
Citation Information
Patent Citations
Novel mesogen-silicon compound (CO)polymer and thermoplastic elastomer
WO2018147010A1
Method for producing connected structure, anisotropic electroconductive bonding material, and connected structure
WO2021079812A1
Novel terminal-modified polyphenylene ether and terminal-modified polyphenylene ether composition
WO2022239631A1